Media multitasking, online vigilance and academic performance among students in three Southern African countries. (January 2021) - le Roux, Daniel B.; Parry, Douglas A.; Totolo, Angelina; Iyawa, Gloria; Holloway, Jacques; Prenter, Andrew; Botha, Liam
Abstract: High levels of Internet-based media use is a defining feature of behaviour among university students. A growing body of evidence indicates, firstly, that their learning activities are characterised by frequent switching between academic content and online media, and, secondly, that this form of behaviour is negatively associated with academic outcomes. It is less clear, however, whether media use and media multitasking in general is associated with academic performance. In the present study we adopted an exploratory frame and a survey-based methodology to investigate this relationship among students from three countries in Southern Africa. In addition to self-reported media use measures, we investigated the predictive capacity of online vigilance on academic performance. Online vigilance is a novel construct which describes individual differences in users' cognitive orientation to online connectedness, their attention to and integration of online-related cues and stimuli, and their prioritisation of online communication. Our findings ( n = 1445 ) indicate a weak, negative association between self-reported media use measures and academic performance, as well as online vigilance and academic performance. Combined, media use and online vigilance predict 9% of variance in academic performance for our full sample. However, when considering only Namibian students ( n = 402 ), they predict 27% of variance. The study findings raise important questions relating to concerns over the potential impacts of general media use behaviours on academic performance among university students. Highlights: Survey data of media use behaviour and academic performance were collected. Measures included media multitasking and online vigilance. University students from three African countries participated (n = 1445). Media use behaviour is associated with lower academic performance (R 2  = 0.09). This association is particularly strong for Namibian students (R 2  = 0.27).